Integrating Artificial Intelligence into Project Management for Efficient Resource Allocation - Mohite, Rajendra; Kanthe, Rajesh; Kale, Kiran S.; Bhavsar, Dhananjay N.; Murthy, D. Narasimha; Murthy, R. A. Dakshina (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Artificial intelligence (AI) has enhanced resource distribution efficiency in project management. Effective resource management is essential to the project’s success since it directly affects the budget, the schedule, and the project’s financial results. The function of AI in maximising resource allocation strategies is examined in this abstract, which also identifies potential advantages and disadvantages. Machine learning and predictive analytics are two instances of artificial intelligence (AI) technologies that enable the analysis of significant amounts of historical project data, team performance indicators, and outside impacts.It is possible to do this by developing sophisticated models that can estimate resource requirements, identify potential roadblocks, and suggest the most effective influence strategies. Project managers can reduce the risks of over-allocation or underutilization by leveraging AI-driven insights to guide their decisions when allocating workers, funds, and other resources. Real-time monitoring and resource distribution correction while a project is in progress are also made possible by AI. To ensure that the resources are adapted to the project’s changing needs, dynamic resource changes can be made in response to changing conditions. This adaptability increases the project’s resistance because it lowers the likelihood of delays or exorbitant costs. The use of AI in project management, however, is not without its difficulties. It is important to carefully evaluate ethical issues including data privacy, bias reduction in algorithmic decision-making, and openness in the justification for resource allocation. Additionally, organisations must spend money on technology infrastructure, personnel training, and change management procedures in order to implement AI.